(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research takes place to discuss the movement of lexicons retouch and it‘s abbreviation in arabic heritage until the eighth century AH , and monitoring it‘s role in supplying the arabic and I slamic civiliztion in value composers integrated with the original compositions in formation of cultural landscape by elevating it to levels of knowledge which is indis putable about their importance. to clarify that displays search polite definition and abbreviation and the reasons of composition them In the arabic heritage, and then mukhtar al-shehah‘s lexicon by " abo bakr al-razi" deals with a selected chapter , provides adescri of the razi‘s abbreviated and relationship to the asset , then razis curriculum taught in the abbreviation and civility , and the research ends reading findings . Which envisages demonstrate added value of these abbrevi on the original lexicons .